Século Virgulino: o cangaço nas (con)fusões da memória entre comemorações de Lampião no tempo presente - Ramos Filho, Vagner Silva (2017)
This paper aims at contributing to the discussion on the culture of the contemporary memory of cangaço. The cangaço, a banditry phenomenon experienced between the second half of the nineteenth century and the first half of the twentieth century in the Brazilian Northeast, ended decades ago, but its memory survived in several cultural backgrounds. The expansion of this controversy memory’s reframing movement, understood as a regional result of an ever-present past, due to carrying in its heart the dilemma of remembering or forgetting, raises intense questioning, especially regarding the different validations that make it a claimed, dissonant and contested cultural heritage. The research goes over its agreements and conflicts between the 1980s and 2010, whose inflection point are the celebrations of Lampião’s birth centenary in the late 1990s, in a fragment marked particularly by the celebrations to this cangaceiro’s death – its fiftieth anniversary ( 1988), sixtieth (1998) and seventieth (2008). The main objective is to question this memories analyzing its (con)fusions in a strengthening period in the public scenario; their battles on centenary celebrations; and its celebrative cults in the festival’s calendar created after the event. The study of these Cangaço’s Memory, in close relationship with the northeastern time, discusses temporal pieces that claim ruptures, continuities and other branches in the imaginary land of the said regional identities. Starting especially with the assumption of the History of Memory, we examine institutions’ performances, groups and individuals, such as former bandits (cangaceiros), family, popular artists, filmmakers, chroniclers, victims, intellectuals and journalists, through some historical sources - focused in the press, but also articulating with official projects, books, twine, brochures, photographs, movies and interviews – which allow us to think about the problems raised. This paper is developed in the Research Group on Heritage and Memory (GEPPM-UFC/CNPq).